Fibrolitic Sillimanite in Sheared Rocks of the Ambela Granitic Complex Northwestern Pakistan - Rafiq, Mohammad; Jan, M. Qasim (Journal of Himalayan Earth Sciences, 1987)
Two-mica granites in the northeastern margin of the Ambela granitic complex underwent cataclastic deformation. The resulting shear zones acted as pathways for the migration of a water-rich fluid phase that also contained boron and some fluorine. This resulted in (1) formation of fibrolitic silimanite and white mica at the expense of feldspars and biotite, especially along micro-shears, (2) bleaching of biotite and release of Fe and Ti oxides, and (3) crystallization of tourmaline and fluorite. Some recrystallization/neo-mineralization of feldspar, quartz and muscovite also occurred due to shearing.